(untitled) (Педагогіка вищої та середньої школи, 2006)
Professional ability as a condition of art - pedagogical preparation of the teacher graphic and arts and crafts substantive provisions of an experimental research process formation of professional ability of the future teacher of the fine arts to art training schoolboys in conditions of system of art - pedagogical education. Are examined.